Elie Wiesel - Berger, Alan L., 1939- author.
1 online resource (xiv, 164 pages)
Keywords: "Elie Wiesel: Humanist Messenger for Peace is part-biography and part-moral history of the intellectual and spiritual journey of Elie Wiesel, a Holocaust survivor, human rights activist, author, university professor, and Nobel Peace Prize winner. In this concise text, Alan L. Berger portrays Wiesel's transformation from a pre-Holocaust, deeply God-fearing youth to a survivor of the Shoah who was left with questions for both God and man. An advisor to American presidents of both political parties, his nearly 60 books voiced an activism on behalf of oppressed people everywhere. The book illuminates Wiesel's contributions in the areas of religion, human rights, literature, and Jewish thought to show the impact that he has had on American life. Supported by primary documents about and from Wiesel, the volume gives students a gateway to explore Wiesel's incredible life. This book will make a great addition to courses of American religious or intellectual thought"--